THE RELATIONSHIP BETWEEN SELF EFFICACY AND THE LEVEL OF KNOWLEDGE OF NURSING PROFESSIONAL STUDENTS AT JENDERAL SOEDIRMAN UNIVERSITY TOWARDS THE IMPLEMENTATION OF BASIC LIFE SUPPORT IN CARDIAC ARREST - Kamaluddin, Ridlwan; Alivian, Galih Noor (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Cardiac arrest is a phenomenon that can happen to anyone, anywhere, and anytime. One of the actions to handle cardiac arrest is to provide basic life support (BLS). Nursing profession students as one of the bystanders and prospective health workers, need to pay attention to crucial things such as knowledge and self efficacy as a basis for performing BLS. This study aims to determine the relationship between knowledge level and self-efficacy towards the application of basic life support in cardiac arrest cases.Methods: This type of research is cross sectional, sampling using total sampling with a total of 70 nursing profession students aged 27 years. The research instrument used a modified knowledge level and self-efficacy questionnaire. The analysis test used the Spearman Rank correlation test.Result: The results of this study showed that the average age of respondents was 22,64 years, (92,9%) the majority were female, (81,4%) had encountered cardiac arrest cases, (61,4%) had performed BLS actions. The level of knowledge of the respondents was in the good category with a percentage of (64,3%) and self efficacy in the high category with a median of 63,5 (category in score52). The results of the Spearman Rank correlation test showed a significant relationship with a p value = 0,026 and a coefficient value of 0,266).Conclusion: There is a significant relationship between the level of knowledge of nursing professional students and self-efficacy towards the application of basic life support in cardiac arrest cases.